2006
DOI: 10.1111/j.1600-0404.2006.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic heart rate variability analysis in idiopathic Parkinson's disease

Abstract: The results indicate that impairment of autonomic nervous system function in IPD without autonomic symptoms is frequent, and does not show clear association with clinical stage and the age of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
3
24
1
Order By: Relevance
“…As for cardiac autonomic abnormalities, sympathetic denervation has been demonstrated by numerous studies employing either 123 I-MIBG myocardial scintigraphy or 6-[ 18 F] fluorodopamine cardiac PET [8,9,[11][12][13]19,20]. Nevertheless, little information is available as to how the involvement of cardiac parasympathetic system develops in PD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As for cardiac autonomic abnormalities, sympathetic denervation has been demonstrated by numerous studies employing either 123 I-MIBG myocardial scintigraphy or 6-[ 18 F] fluorodopamine cardiac PET [8,9,[11][12][13]19,20]. Nevertheless, little information is available as to how the involvement of cardiac parasympathetic system develops in PD.…”
Section: Discussionmentioning
confidence: 94%
“…This implies a need for a comprehensive understanding of cardiovascular autonomic status including cardiac parasympathetic and peripheral vasomotor activity and cardiac sympathetic function. Despite the presence of several hemodynamic studies showing the involvement of cardiac parasympathetic system in PD [9][10][11][12][13], its incidence and temporal profile relative to cardiac sympathetic denervation remain elusive.…”
Section: Introductionmentioning
confidence: 96%
“…Studies have demonstrated that a deficiency in cardiovascular autonomic control occurred in the beginning of the disease [23,24]. Researchers evaluated patterns of tonic cardiovascular control by lower results for SDNN and reported deregulation in new patients, even not treated, and advanced ones [25].…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing HRV in untreated PD and control subjects found that HRV was decreased in PD when the patients were awake and while asleep [51]. A decrease in HRV in PD patients was found in those without any autonomic symptoms [52].…”
Section: Heart Rate Variability (Hrv)mentioning
confidence: 99%